Spiritual Guidance Has an Effect on Decreasing The Level of Anxiety in Mothers During The First Stage of Labor - Weni Guslia Refti; Muji Lestari; Andriansyah Andriansyah; Desi Rosdian; Nina Herlina (Universitas Andalas, 2023)
The birth process is a physiological event. Every mother who will give birth will experience pain as a manifestation of the baby's birth process. The effects of pain experienced by the mother will cause anxiety which often has a negative impact on birth outcomes. Many ways to deal with anxiety during labor are related to reducing pain, but only a few have researched the effect of spiritual guidance on reducing this pain. This study aims to assess the effect of spiritual guidance on the level of anxiety in mothers in the first stage of active labor. This study used a one-group pretest and post-test pre-experimental design on 71 mothers in the first active phase of labor. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HSRA). The statistical analysis used is Wilcoxon. The results of the study found that there was a decrease in anxiety from before and after being given spiritual support to mothers in the first stage of labor. It is very important to provide childbirth support such as spiritual guidance to birth mothers in reducing their anxiety levels